PRINCIPLES OF CONSIDERING OF ERGONOMIC INDICATORS IN INCLUSIVE DESIGN OF THE ENVIRONMENT - Чупріна, Н. В.; Булатов, В. А. (Art and Design, 2023)
Purpose: definition of the criteria for the implementation of ergonomic indicators in the inclusive design of the environment.Methodology. The methods of comparison and generalization, complex and systematic analysis, which helped to define the principles and characterize the means of taking ergonomic indicators into account in the inclusive design of the environment are used in the research.Results. The analysis of the principles of taking into account ergonomic indicators in the inclusive design of the environment was carried out. Their influence on the formation of inclusive design products during the development of the subject-spatial environment is determined. The expediency of systematization and generalization of information about the basic approaches and means of inclusive design with the aim of creating a generalized typology of the latest methods and measures in the formation of visual and design solutions is substantiated.Scientific novelty consists in determining the principles of using ergonomics requirements in the formation of modern products and the spatial environment of inclusion is the main principle and goal in creating a comfortable, safe, accessible and aesthetic design product for people with disabilities. It is proposed to create platforms for the analysis of the achievements of inclusive design products for people with disabilities, which will open up new opportunities for the creation of modern inclusion ergodesign products.Practical significance. The conducted analysis made it possible to determine the principles of taking ergonomic indicators into account in the inclusive design of the environment and the means of their further use in the creation of a subject-spatial environment.